Human neutrophil extracellular traps do not impair in vitro Toxoplasma gondii infection - Macedo, Isabela S.; Lara, Flávio A.; Barbosa, Helene S.; Saraiva, Elvira M.; Menna-Barreto, Rubem F. S.; Mariante, Rafael M. (Frontiers in Immunology, 2023)
Toxoplasma gondii, responsible for causing toxoplasmosis, is a prevalent food and waterborne pathogen worldwide. It commonly infects warm-blooded animals and affects more than a third of the global human population. Once ingested, the parasite enters the host's small intestine and rapidly disseminates throughout the body via the bloodstream, infiltrating various tissues. Leukocyte-driven responses are vital against T. gondii, with neutrophils playing a dual role: swiftly recruited to infection sites, releasing inflammatory mediators, and serving as a replication hub and Trojan horses, aiding parasite spread. Neutrophils from various hosts release extracellular traps (NETs) against the protozoan. However, gaps persist regarding the mechanisms of NETs production to parasite and their significance in infection control. This study investigates the interplay between human neutrophils and T. gondii, exploring dynamics, key molecules, and signaling pathways involved in NETs production upon protozoan challenge. Using confocal and electron microscopy, live cell imaging, pharmacological inhibitors, and DNA quantification assays, we find that human neutrophils promptly release both classical and rapid NETs upon pathogen stimulation. The NETs structure exhibits diverse phenotypes over time and is consistently associated with microorganisms. Mechanisms involve neutrophil elastase and peptidylarginine deiminase, along with intracellular calcium signaling and the PI3K pathway. Unexpectedly, human traps do not diminish viability or infectivity, but potentially aid in capturing parasites for subsequent neutrophil phagocytosis and elimination. By revealing NETs formation mechanisms and their nuanced impact on T. gondii infection dynamics, our findings contribute to broader insights into host-pathogen relationships.